Waist-to-height ratio and new-onset hypertension in middle-aged and older adult females from 2011 to 2015: A 4-year follow-up retrospective cohort study from the China Health and Retirement Longitudinal Study - Wu, Yang; Tong, Yingmu; Wang, Hai; Zhang, Xing; Long, Yunxiang; Li, Qinglin; Ren, Jie; Liu, Chang (Frontiers in Public Health, 2023)
Background: Central obesity was closely associated with hypertension. Middle-aged and older adult females, defined as those aged 45 and above, were more likely to suffer from central obesity. For waist-to-height ratio (WHtR) was used as central obesity assessment, the object of this study was to illustrate the relationship between WHtR and the incidence of hypertension in middle-aged and older adult females in China. Methods: Data used in this prospective cohort study was derived from the China Health and Retirement Longitudinal Study (CHARLS) in a baseline survey from 2011 to 2012 with a follow-up duration of four years. The waist-to-height ratio was calculated as waist circumstance divided by height, and the cohort was divided into different groups based on WHtR level. The outcome variable was new-onset hypertension. Results: Of the 2438 participants included in the study, 1821 (74.7%) had high WHtR levels (WHtR >= 0.5). As WHtR was closely related to new-onset hypertension in a multivariable logistics regression mode (OR:7.89 [95%CI:2.10-29.67]), individuals with high WHtR were also more likely to suffer from hypertension compared with low WHtR levels (OR: 1.34 [95% CI:1.06-1.69]). Conclusion: WHtR is positively related to the risk of hypertension incidents among middle-aged and older adult females. Individuals with WHtR >= 0.5 were more likely to suffer from hypertension.